2019
DOI: 10.15244/pjoes/102627
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Granular and Liquid Insecticides against <i>Chilo partellus</i> on Maize in Pakistan

Abstract: Considering the economic importance of the maize Zea mays (Poales: Poaceae) crop and the losses caused by the maize stem borer, an experiment was carried out in a plot of 15 m 2 that was equally divided into three replications using randomized complete block design to find the effect of granular and liquid insecticides on Chilo partellus and crop yield. The trial was laid out at the Agricultural Research Station in Baffa, Mansehra, Pakistan during the Kharif season 2015. In this experiment, granular insecticid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The results of my research work are different from the results ofa few research workers as well. Khan et al (2020) described that granular insecticide carbofuran 3G was noticed as the most effective amongst all tested insecticides while in my research work, Chlorpyriphos 40EC was superior ineffectiveness against C. partellus. Singh et al (2014) found that cypermethrin was highly effective against C. partellus.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The results of my research work are different from the results ofa few research workers as well. Khan et al (2020) described that granular insecticide carbofuran 3G was noticed as the most effective amongst all tested insecticides while in my research work, Chlorpyriphos 40EC was superior ineffectiveness against C. partellus. Singh et al (2014) found that cypermethrin was highly effective against C. partellus.…”
Section: Resultsmentioning
confidence: 79%
“…Therefore practical demonstration of such promising toolsforinsect pest management in farmers' fields and economic evaluation of dissimilar insecticidal treatment is essential (Cugala et al, 2006;Bhandari et al, 2016) A wide range of insecticide chemistries and preparations have been used to control this insect pest (Saeed et al, 2006). Liquid and granular type of insecticides have been found effective against C. partellus (Khan et al, 2020). Granular formulations of carbofuran and chlorpyriphos were described as operative against the pest by Bhat and Baba (2007).…”
mentioning
confidence: 99%
“…All other cropraising practices were carried out to ensure healthy crop and no insecticides other than those comprised in the experiment were practiced. The granular insecticides were applied in the leaf whorls afterward 15 days of germination when the crop was more than 4 leaf stage (Khan et al, 2020). The area of single experimental unit was 578 m 2 .…”
Section: Crop Husbandrymentioning
confidence: 99%
“…Whilst studies have presented the quest for clean and afford energy by household in developing countries has a problem (Jan, Khan, & Hayat, 2011;Ren et al, 2022), Covert et al, (2016) noted that in developing countries there are few policies on the use of fossil fuel despite the raising cases of air pollution. In fact, Debebe et al (2023) pointed out that ensuring energy security and containing the contribution of energy use to environmental changes remain a source of concern in most African states because of the continuous reliance of about 900 million households on the use of biomass fuel for cooking.…”
Section: Household Energy Choice and Climate Change Concerns In Devel...mentioning
confidence: 99%